Rola regionalnych strategii innowacji w podnoszeniu konkurencyjności regionu - Markowska, Małgorzata (Implementation of regional innovation strategies and their role in enhancing region's competitiveness, 2005)
The development and implementation of Regional Innovation Strategies is one of the tools for the development of regions’ innovation policy. The hereby article is an attempt to present methodology for the construction of RIS and to emphasize the significance of innovation for the region’s development, based on an example of selected Regional Innovation Strategies undergoing implementation in Poland.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1095, s. 72-83